The importance of bonding in intralayer carbon fibre/self-reinforced polypropylene hybrid composites. (September 2015) - Swolfs, Yentl; Shi, Jia; Meerten, Yannick; Hine, Peter; Ward, Ian; Verpoest, Ignaas; Gorbatikh, Larissa
Abstract: Polymer composites are usually either stiff or tough, but seldom both. Intralayer hybrids of carbon fibre and self-reinforced polypropylene (PP) do offer the potential to achieve a unique combination of toughness and stiffness. In these hybrids, the bonding between carbon fibre prepregs and PP tapes is a crucial parameter. For a weak bonding, the 20% ultimate tensile failure strain and high penetration impact resistance of self-reinforced PP were maintained. For a strong bonding, the ultimate tensile failure strain was strongly reduced, but the flexural performance was improved. For a homopolymer PP matrix in the prepregs, the weak bonding between fibre and matrix caused the penetration impact resistance to reduce according to a linear rule-of-mixtures. For a maleic anhydride modified PP matrix however, the strong fibre–matrix bonding greatly reduced the penetration impact resistance. These results provide new insights into designing hybrid composites with a unique balance of stiffness and failure strain.